Factors affecting successful scale-up of health-related pilot projects - Mariam Ashraf; Aniza Ismail; Idayu Badilla Idris; Inayat Thaver (Journal of the Pakistan Medical Association, 2020)
Objective: To identify the key factors that contribute to the successful scale-up of pilot projects, with emphasis on factors that are proven helpful in the successful scaling up of health interventions. Methods: Grey literature was searched at the library of the University of Kebangsaan, Malaysia, on database engines Google Scholar and Science Direct with specific key words to screen papers published from January 2001 to June 2016. They were reviewed to identify the key factors affecting scaling up of health-related pilot projects. Full-text articles were selected, and their reference lists were checked to look for relevant papers. They were short-listed and analysed using thematic approach. Results: Of the 47 articles initially screened, 14(29.78%) were shortlisted. Thematic analysis of the selected articles suggested several key factors contributed to the successful scale-up of pilot projects. These factors included evidence-based and effective intervention, community readiness, Continuous....